1985
DOI: 10.1111/j.1476-5381.1985.tb08845.x
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro pharmacology of xamoterol (ICI 118,587)

Abstract: IThe effect of xamoterol and (-)-isoprenaline have been compared for their activity at padrenoceptor sites in a number of in vitro cardiac and smooth muscle preparations. 2 Xamoterol produced weak positive chronotropic effects in guinea-pig, rat and cat atria (intrinsic activity < 0.55, ( -)-isoprenaline = 1). Positive inotropic effects were obtained in driven left atria of the cat but were absent in guinea-pig left atrial and right ventricular strip preparations. Agonistic effects were due to P,-adrenoceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 23 publications
(25 reference statements)
3
25
0
Order By: Relevance
“…This is consistent with pA 2 values reported by Strosberg (1997). Likewise, xamoterol (␤ 1 agonist) (Malta et al, 1985), causes a concentration-dependent relaxation of the IAS smooth muscle that is selectively antagonized by CGP 20712A (␤ 1 -AR antagonist).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with pA 2 values reported by Strosberg (1997). Likewise, xamoterol (␤ 1 agonist) (Malta et al, 1985), causes a concentration-dependent relaxation of the IAS smooth muscle that is selectively antagonized by CGP 20712A (␤ 1 -AR antagonist).…”
Section: Discussionsupporting
confidence: 80%
“…The ␤ 1 -AR agonist xamoterol (Malta et al, 1985) produced a concentration-dependent fall in the basal tension of the IAS smooth muscle (Fig. 3A) with an EC 50 value of 1.02 ϫ 10 Ϫ7 M (n ϭ 5-8).…”
Section: Effect Of Xamoterol On the Basal Tone Of Ias Smooth Musclementioning
confidence: 99%
“…In contrast, xamoterol rescues contextual memory retrieval in NE-deficient Dbh 2/2 mice at 0.3 and 1 mg/kg. The potency of xamoterol for b 1 relative to b 2 receptors is 10-fold in rat tissue ex vivo and at mouse adrenergic receptors in vitro (Malta et al 1985;Beer et al 1988;Murchison et al 2004). As a result, we hypothesized that the higher doses of xamoterol activate b 2 as well as b 1 receptors and that the activation of b 2 receptors impairs retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have confirmed that denopamine has a high intrinsic activity on P1-adrenoceptors, even if it is not a full agonist. Thus, the high intrinsic activity of denopamine seems to be responsible for it acting as an agonist in man (Hori et al, 1991 , 1987), uterus and ileum (Malta et al, 1985) and in the dog femoral artery (Nuttall & Snow, 1982) which are all P2-adrenoceptor containing preparations. Moreover, denopamine and xamoterol, when tested for antagonist activity in the right atria and trachea, exhibited different pA2 values, indicating that both agonists show PI-and P2-adrenoceptor antagonist actions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we have studied the pharmacological properties of T-0509 by using guinea-pig cardiac muscle, trachea and aorta as systems with functions of fI-, P2-and a-adrenoceptors (Buckner & Patil, 1971;Patil et al, 1971;1972;Malta et al, 1985;Hattori et al, 1987), respectively.…”
Section: Introductionmentioning
confidence: 99%